Analysis of The Feasibility Study for The Culinary Business of Culinary Tourism in Kali Mojo, Tegalwaton, Semarang Regency - Nur Ifa Maulida; Rahayu Ambarwati; Astri Dian Utami; Komala Inggarwati (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
Tegalwaton Village has potential that can be developed to become a tourist attraction. One of them is the Kali Mojo area which is located near the Tingkir toll exit. For now, Kali Mojo is managed by the Kingstone youth organization in the area. The potential of Kali Mojo has a good opportunity to become a culinary tourism center. This study was conducted to assess the development of culinary tourism in Kali Mojo from the market and financial aspects. The results show that the culinary tourism development plan in Kali Mojo has a large market potential and is financially profitable so it is possible to run.